Priming determinist beliefs diminishes implicit (but not explicit) components of self-agency - Lynn, Margaret T.; Muhle-Karbe, Paul S.; Aarts, Henk; Brass, Marcel (Frontiers in Psychology, 2014)
Weakening belief in the concept of free will yields pronounced effects upon social behavior, typically promoting selfish and aggressive over pro-social and helping tendencies. Belief manipulations have furthermore been shown to modulate basic and unconscious processes involved in motor control and self-regulation. Yet, to date, it remains unclear how high-level beliefs can impact such a wide range of behaviors. Here, we tested the hypothesis that priming disbelief in free will diminishes the sense of agency, i.e., the intrinsic sensation of being in control of one’s own actions. To this end, we measured participants’ implicit and explicit self-agency under both anti-free will and control conditions. Priming disbelief in free will reduced implicit but not explicit components of agency. These findings suggest that free will beliefs have a causal impact on the pre-reflective feeling of being in control of one’s actions, and solidify previous proposals that implicit and explicit agency components tap into distinct facets of action awareness.